Thermal activation on phase formation of alkaline activated kaolin based system - Somsak Boonjaeng (2018)
The research aim was to investigate phase development after pozzolanic reaction between metakaolin (MK) and calcium hydroxide (CH) with alkaline and thermal activations. The CH to MK ratio (C/M) of 0.4 generating CaO/SiO2 of 1.18 was selected in this study. Various concentrations of NaOH solutions (0.01, 0.1, 1, 3, 5 and 10 M) were used. The alkali activated samples were thermally activated at 25 °C, 70 °C, 90 °C and 130 °C for 4 h. Phase development under thermal activation of alkali activated metakaolin based system were investigated. At every temperature, C/M mixtures with 0.01 and 0.1 M NaOH promoted the formations of poorly crystalline calcium silicate hydrate (C-S-H(I)) and calcium aluminosilicate hydrate (CASH) compounds. With 3 and 5 M NaOH activations, sodium aluminosilicate hydrate (NASH) and sodium calcium silicate hydrate (NCSH) was formed. 1 M NaOH was found to be a boundary of phase transformation from C-S-H(I) and CASH to NASH and NCSH. In addition, zeolite X and sodalite appeared when NaOH solution reached 10 M. Thermal activation significantly affected phase development at high concentration of alkaline activation (1-10 M). At 1 M NaOH, NASH compounds in a form of gmelinite and zeolite ZK-14 were found at 70-90 °C. At 3-5 M, katoite was found at 70-130 °C. At 10 M, zeolite X was found at 70-90 °C. Sodalite was also found at 130 °C with 10 M NaOH. © (2013) Trans Tech Publications, Switzerland.